Peaceful negotiations and the right of self-determination: A case study of Iraqi Kurdistan region - Oseni, Umar Aimhanosi (2013)
In seeking for the right of self-determination, a preconceived notion born out of historical facts is its inherent conflicting nature. A move to address the right of self-determination in a manner that engenders peacebuilding through good faith negotiations and good offices which represent the core of conflict management appears to be more appealing in the modern world. Against this backdrop, this paper examines the right of self-determination as recognized in international law in the light of peacebuilding initiatives with specific reference to the Kurdistan Region of Iraq. An oil rich region of this kind is always a subject of conflicts despite its regional autonomy. Referendum about the federal region is a step towards conflict management but there is more to the tension between Erbil and Baghdad. It is argued that the right to self-determination of the Kurds must be asserted, supported and actively implemented through peaceful means. The international community has a great role to play in easing the tension between the region and the national government in Iraq. While relying on the fundamental principle established in Chapter VI of the UN Charter on the pacific settlement of disputes, this paper looks at the UN mechanism for managing such disputes including the Manila Declaration on the Peaceful Settlement of International Disputes 1982. The paper concludes that the right of self-determination and peaceful settlement of disputes are fundamental principles of international relations which cannot be bifurcated in any way. Such inextricable harmony between the two principles must be sustained for a peaceful world order.